Education About English Competencies Needed by Nursing Students of Baiturrahim Vocational School Jambi - Warahmah, Mawaddah; Junaidi, Adi Saputra; Hasmar, Wanti (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2023)
English is an international language that is very important in communicating, especially in the health sector. This implies that it is necessary to master English appropriately to respond to intensive interactions in every country, especially in the global era. Therefore, as the most widely spread international language, mastery of English is a must. In Indonesia, English is still seen as a luxury language. The reason why English is included as a subject in elementary schools, as a basis, is that English should be a necessity for students in their future, especially in the era of globalization. This Community Service (PkM) aims to educate the English language competencies needed by nursing students in learning English to prepare them to continue their health education and become nurses at an international level. The competencies needed by students and nurses will later be used for the future of students majoring in nursing at Baiturrahim Vocational School. This community service takes place at Baiturrahim Vocational School. This educational method uses the approach of providing materials and leaflets to students and teachers at Baiturrahim Jambi Vocational School which is located at Jalan H. Syamsoe Bachroen No. 32 RT. 04, Selamat District. Sipin Lake, Jambi City, Jambi Province. This series of service activities has started in September 2022 - March 2023. The results of this education include increasing students' knowledge about the ten main competencies that nursing students must master in order to function well in the nursing profession.